The effects of polysaccharides from the root of Angelica sinensis on tumor growth and iron metabolism in H22-bearing mice. Issue 2 (13th January 2016) - Cheng, Yao; Zhou, Jiali; Li, Qiang; Liu, Ying; Wang, Kaiping; Zhang, Yu
Abstract : ASP could participate in the regulation of iron metabolism to induce an inhibitory effect on tumor growth by decreasing the levels of hepcidin, IL-6, ferritin, Tf, TfR1 and TfR2 in H22-bearing mice. Abstract : The crude polysaccharide was obtained from the root of Angelica sinensis (AS) to investigate its effect on tumor growth and iron metabolism in H22-bearing mice. In our study, we showed that Angelica sinensis polysaccharide (ASP) was mainly composed of arabinose, glucose and galactose in a molar ratio of 1 : 1 : 1.75, with a molecular weight of 80 900 Da and a sugar content of 88.0%. Animal experimental results revealed that three doses of ASP all had anti-tumor effects with inhibition ratios of 27.11%, 31.65% and 37.05%. With respect to iron metabolism, the mean levels of serum hepcidin, interleukin-6 (IL-6), ferritin, transferrin (Tf), transferrin receptor 1 (TfR1) and transferrin receptor 2 (TfR2) in H22-bearing mice were promoted, and serum iron concentration decreased significantly. After treatment with ASP, these iron-related indicators recovered in different degrees. The findings suggested that the anti-tumor activity of ASP may be affected by its regulation on iron metabolism in H22-bearing mice.